Shortening Recovery Time with Bypass Breaker for Resistive Superconductor Fault Current Limiters - Yilmaz, Bugra; Gencoglu, Muhsin Tunay (Springer Heidelberg, 2023)
Many modern limiting methods have been developed for power systems in recent years. Resistive superconductor fault current limiter (R-SFCL), one of the modern limiting methods, has advantages such as small size and low cost. R-SFCL, which theoretically transmits energy without loss in normal operation, becomes high resistance in case of fault and reduces fault current level. However, R-SFCL, which rapidly increases its resistance during a fault, cannot immediately switch to superconductivity after the fault. During this period, which is called the recovery time, R-SFCL causes unwanted voltage drops and power losses under normal operating conditions. Therefore, recovery time is an important design parameter that should be kept short. With the bypass breaker proposed in this study, the recovery time was shortened, and voltage stability was improved. In addition, the system's reliability is increased by providing breakers' controls from two different points instead of a single point. This method is a hybrid system where limiting and protection elements are combined in one system. Modeling and simulations were performed in MATLAB/Simulink.
Keywords: Dynamic model; Fault current; Fault current limiting; MATLAB; Simulink; Recovery time; R-SFCL; Superconductor